P5-S7.15 STI knowledge and testing practices among FSW working outside of the main entertainment district in Tijuana, Mexico. (10th July 2011) - Rusch, M; Gallardo, M; Lozada, R; Mercer, V J; Zuniga, M L; Patterson, T L; Strathdee, S A
Abstract : Background: Regular sexual healthcare among FSW is important to reduce transmission and susceptibility of STIs and to enable earlier intervention and treatment for HIV and cervical cancer. Test and treat programs may improve access to sexual health services; however, low STI knowledge and risk perceptions may impede use of available services. We assessed the relationship between STI knowledge and testing among FSW in Tijuana, Mexico. Methods: Proyecto Amantes de la Salud (Lovers of Health) conducted baseline surveys among 403 FSW working in bars outside of Tijuana's red light district using time-location sampling. Surveys included demographics, sexual behaviour, sex work characteristics and sexual healthcare and a 28-item STI knowledge scale (Jaworski and Carey, 2007). Adjusted prevalence ratios were estimated using poisson regression to assess the association between STI testing in the past year and standardised STI knowledge scores. Results: Participants were aged 18–55 years (Median: 28; IQR: 23–32), all born in Mexico and had been involved in sex trade a median of 6 years (IQR: 3–9). A majority (69%) reported having an STI test in the past year and 39% reporting three or more tests see Abstract P5-S7.15 table 1 . Median STI knowledge score was 63% (IQR: 55–70). Notably, 43% and 33% did not think there were cures for Chlamydia and gonorrhoea, respectively. Among the 31% with no STI test, 87% (N=95) indicated that this was because they "had been careful/always used condoms". However, of these, only 44% reported consistent condom use for vaginal sex with non-regular clients. In adjusted regression models accounting for education, income, years in sex work, number of clients and self-treatment, higher STI knowledge scores remained significantly associated with STI testing. Discussion: STI knowledge was significantly associated with reporting STI testing in the past year. As women work in bars and brothels outside of the main entertainment district where the majority of FSW interventions are based, STI knowledge may have a greater impact on access and utilisation of testing services. Importantly, misperceptions regarding available treatment and perceptions of sexual risk were prevalent. Incorporation of sexual health education into existing HIV/STI programs is warranted and would be an efficient way to improve sexual healthcare in this population.